Analisis Isi Sinetron Cinta Setelah Cinta di Sctv Dalam Perspektif Gender - Firdaus , Ilyas; Manalullaili; Muslimin (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
In this research the researcher will use a critical paradigm. The critical paradigm seeks to combine theory and action (praxis) consciously. "Praxis" is a central concept in the critical philosophical tradition. According to Habermas, praxis is not blind behavior based on mere instinct, but rather the basic action of humans as social creatures. The critical approach used by researchers in analyzing the soap opera Cinta After Cinta is based on Roland Barthes' theory. The critical approach used by researchers in analyzing the soap opera Cinta After Cinta is based on Roland Barthes' theory. Meanwhile, the type of research used in this research is Roland Barthes' semiotic analysis model. This model was chosen because the researcher wanted to describe the markers and signifieds contained in the soap opera Cinta After Love, as well as describe the gender perspective regarding roles, status, nature and decision making contained therein. The analysis in this research is audio and visual, namely scenes and dialogues that show a gender perspective in the soap opera Cinta After Cinta. In this research, researchers will use the term scene to describe the gender perspective that occurs in the soap opera Cinta After Cinta. Where a scene is a piece of a film consisting of scenes and dialogue. In this research, researchers will use shots as image composition. This discussion contains a report on the results of the analysis carried out by researchers regarding gender perspectives in the soap opera Cinta After Cinta. This researcher uses gender perspective theories related to literalist, moderate, and progressive. Meanwhile, there will be four indicators that will be studied, namely role, status, nature and decision making between men and women (husband and wife). Overall, in this research on the soap opera Cinta After Love, there is still a lot of gender inequality between men. and women. Where a husband still dominates or is "Literalist" in married life, as can be seen in the "status, nature and decision making" scene, and in this research there is only one gender perspective which is "Progressive" which describes the similarities between husband and wife, namely in terms of "roles".